(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
The importance of assisting verbs in the Uzbek language is examined in this article, with an emphasis on their function in second language acquisition (SLA). Auxiliary verbs, sometimes known as helping verbs, play important grammatical roles in the construction of aspect, tense, and mood—all of which are necessary for clear communication. The examination makes use of a number of linguistic frameworks, instructional techniques, and empirical research to show how learners of Uzbek as a second language can improve their proficiency by comprehending and applying helpful verbs.